Participatory process to design community-driven solutions for reducing antibiotic use in chicken production in Vietnam - Bâtie, C.; Luong Hung Nam; Anh Ta Phuong; Trang Thi Pham; Molia, S.; Phuc Pham Duc; Goutard, F. (Public Library of Science, 2025)
International organizations emphasize the urgent need to reduce antibiotic use to combat antimicrobial resistance, including in livestock farming. Technical, regulatory, and awareness-raising strategies exist, but they often fail due to a misalignment with farmers’ realities. We hypothesize that actively engaging communities in the design of solutions will more effectively reduce antibiotic usage. We have therefore adapted and applied the ImpresS ex ante approach (impact of research in the South), to co-design solutions with stakeholders from the chicken and veterinary value chain at a local level in Vietnam. Eighteen participants (chicken farmers, drug sellers’ representatives, public and private veterinarians, a chicken retailer, and academic staff), working at the communal, district, or provincial level, were involved in three half-day workshops organized in Thai Nguyen province in April 2022. Through this participatory process, participants collectively envisioned a 10-year future with reduced antibiotic use in chicken farms. They identified barriers including the lack of outlets for organic meat products, lack of knowledge and awareness of biosecurity and organic farming, low compliance of small-scale farms with biosecurity, and lack of science and technology related to alternative products. Participants decided to address “knowledge gaps” barrier. They have designed two strategies to improve the training of farmers and drug sellers, so that it is closer to the chicken value chain realities and reaches a greater audience. In this study, we identify systemic barriers to reducing antibiotic use, while recommending practical solutions. We also advocate the need to include locally-developed solutions in the national action plan on antimicrobial resistance in Vietnam and to involve policy-makers in participatory processes to design effective strategies.